2020
DOI: 10.1590/s2179-975x0119
|View full text |Cite
|
Sign up to set email alerts
|

Diet of Phylloicus (Trichoptera: Calamoceratidae) caddisfly larvae in forest streams of western Pará, central Brazilian Amazonia

Abstract: Aim The aquatic larvae of the Phylloicus (Trichoptera: Calamoceratidae) caddisflies are typical shredders. However, the trophic classification of Phylloicus has been based on the morphology and behaviour of the larvae. The aim of this study was to investigate the diet of caddisfly larvae Phylloicus in streams. Methods In order to provide a more reliable classification of Phylloicus diet, we analyzed the stomach contents of 185 larvae collected, sampled with D-frame entomological net from 18 streams located in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…It is highly probable that the set of Triplectides larvae collected belonged to a narrower group of species. Studies (Clair, 1994;Pimentel et al, 2020) report both Phylloicus and Triplectides as little selective and the availability of food items is the greatest influence on their diet. Phylloicus are detritivores, being shredders only for breaking down leaves for shelter construction (Pimentel et al, 2020), another explanation for the higher diversity of fungi in DT of this genus as compared to Triplectides.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly probable that the set of Triplectides larvae collected belonged to a narrower group of species. Studies (Clair, 1994;Pimentel et al, 2020) report both Phylloicus and Triplectides as little selective and the availability of food items is the greatest influence on their diet. Phylloicus are detritivores, being shredders only for breaking down leaves for shelter construction (Pimentel et al, 2020), another explanation for the higher diversity of fungi in DT of this genus as compared to Triplectides.…”
Section: Discussionmentioning
confidence: 99%
“…Several taxa showed higher frequencies in specific substrates, which are related to the nature of the occupied substrate, water flow speed, and food resource type. For example, Progomphus (Odonata) has been reported to be associated with sandy substrates, and this genus' nymphs burrow and are adapted to prey on other animals buried in the sandy substrate [84,85], a pattern that has been reported to be linked to the substrate's characteristics and the feeding resource type it contains [86].…”
Section: Relationship Between Physico-chemical Parameters and Och Tra...mentioning
confidence: 99%
“…ii) Shredders with a case have higher consumption and survival rates because removing the case can cause stress due to impaired thermal regulation and respiration (Houghton et al 2014). However, the oxygen levels will not affect shredder consumption or survival, as these organisms are abundant in pools and backwaters in forested streams with high dissolved oxygen (range to 6.8 mg/L; Martins et al 2015;Pimentel et al 2020;Firmino et al 2021) but can also be found in urban streams with low dissolved oxygen (e.g., 2.6 mg/L; Martins et al 2017b). iii) Shredders have higher consumption and survival rates in microcosms with stream water than bottled water due to the similarity of the water characteristics to their natural environment.…”
Section: Introductionmentioning
confidence: 99%